Optimización de procesos como mejoramiento continuo para la fabricación del cuero en la empresa “Curtiembre Quisapincha”. - Quinde Camacho, Julio Medardo. (2021)
The present research aims to the productive processes optimization, analyzing the times of production of leather in the company “Curtiembre Quisapincha.” Therefore, there were applied several tools of measurement and analysis of the current productive index and the production process that uses the company. Besides, the analysis of the data gathering served to raise a proposal for continuous improvement. The optimization is proposed according to experimental and field research approaches, where tools such as the observation of the current production processes managed by the company are applied, to then proceed to the documentary-bibliographic review for the evaluation of productivity. The results obtained from the analysis of the process flow diagram and flow chart, allowed to identify the number of necessary and unnecessary activities to carry out the production of leather. Likewise, the operational problems in the production processes such as operational performance according to the payment of labor, payment of diesel and payment of electricity supply in the company. Then, the proposal is developed through the elaboration of process flow diagrams, analytical diagram, route diagram, the LAYOUT of the plant and a production matrix. This will allow the statistical control of leather production in the company on a daily, weekly, monthly and/or annual basis. In conclusion, the company presents particularities in the activities such as unnecessary transports and unproductive times. With the proposal of the production master plan, it is expected that the statistical controls of production in the company will improve, improving the production capacity and generating more income.